A double-sided flame-retardant type aluminum foil rib composite film and a preparation method thereof

CN119928357BActive Publication Date: 2026-10-30WUXI QIANTE INSULATION MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411956049.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-28
Publication Date
2026-10-30
Estimated Expiration
2044-12-28

AI Technical Summary

Benefits of technology

(1)本发明公开了双面阻燃型铝箔夹筋复合膜材料及其制备方法,方案结构设计合理,产品中采用粘结、阻燃性能优异的压敏胶,因而铝箔贴面之间的剥离强度更高,同时产品具有较优异的阻燃性能,实用性更高。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a double-sided flame-retardant type aluminum foil rib composite film and a preparation method thereof, and relates to the technical field of rib aluminum foil facing. The application takes glass fiber mesh cloth as a base material, coats flame-retardant pressure-sensitive adhesive on both sides, covers the composite film with the same area of the glass fiber mesh cloth, coats the flame-retardant pressure-sensitive adhesive on one side of the aluminum foil, and covers the carbon fiber film with the same area. The flame-retardant pressure-sensitive adhesive comprises 8-12 parts of alkenylized starch, 25-35 parts of functional monomer, 10-14 parts of hydroxyl silicone oil, 10-20 parts of isocyanate acrylate, 25-35 parts of acrylic acid, 0.2-1 part of initiator, 3-10 parts of hydrotalcite, and 3-10 parts of magnesium hydroxide in terms of weight fraction. The application can prepare the flame-retardant pressure-sensitive adhesive with excellent flame retardancy, adhesion and tackiness by properly adjusting the amount of the pressure-sensitive adhesive, and can prepare the final product by combining the aluminum foil, the glass fiber mesh cloth and the carbon fiber film without any solvent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of reinforced aluminum foil lamination technology, specifically to a double-sided flame-retardant reinforced aluminum foil composite film and its preparation method. Background Technology

[0002] Aluminum foil cladding, also known as barrier film, heat insulation film, or heat insulation foil, provides thermal insulation, waterproofing, and moisture resistance. It is widely used for roofing and exterior wall insulation, primarily as insulation material for heating and cooling equipment pipes, and as an outer protective layer for sound-absorbing and sound-insulating materials in buildings, as well as for rock wool and ultra-fine glass wool, providing flame retardancy, corrosion resistance, heat insulation, and sound absorption. Aluminum foil cladding often uses pressure-sensitive adhesive to bond different materials together.

[0003] In existing technologies, pressure-sensitive adhesives are adhesives that can firmly bond to the substrate simply by applying pressure, without requiring temperature, moisture, or ultraviolet light. Due to their dry tack and peelable properties, pressure-sensitive adhesives are widely used in packaging, office labels, and protective insulating tapes for electronic appliances. However, for aluminum foil lamination, multiple properties such as flame retardancy, corrosion resistance, heat insulation, and sound absorption are required. Furthermore, in applications in construction and pipelines, the multiple layers of film within the aluminum foil lamination must be firmly bonded and not easily detached. Therefore, stringent performance requirements are placed on pressure-sensitive adhesives, including high peel strength, excellent flame retardancy, and tackiness. Summary of the Invention

[0004] The purpose of this invention is to provide a double-sided flame-retardant aluminum foil reinforced composite film and its preparation method, so as to solve the problems existing in the prior art.

[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a double-sided flame-retardant aluminum foil reinforced composite film, which uses fiberglass mesh as the substrate, is coated with flame-retardant pressure-sensitive adhesive on both sides, and covers a composite film with an area equal to that of the fiberglass mesh. The flame-retardant pressure-sensitive adhesive comprises, by weight, 8-12 parts of alkenylated starch, 25-35 parts of functional monomers, 10-14 parts of hydroxyl silicone oil, 10-20 parts of ethyl isocyanate acrylate, 25-35 parts of acrylic acid, 0.2-1 parts of initiator, 3-10 parts of hydrotalcite, and 3-10 parts of magnesium hydroxide. The composite film is made by coating one side of an aluminum foil with flame-retardant pressure-sensitive adhesive and then bonding it with an equal area carbon fiber film.

[0006] This invention incorporates hydroxyl silicone oil, whose hydroxyl groups enhance compatibility with acrylic monomers and promote charring of propylene-based pressure-sensitive adhesives, thereby improving the flame retardant effect of the pressure-sensitive adhesives. It rapidly decomposes at high temperatures, releasing a large amount of inert gas to form a protective film that effectively isolates the flame from air, preventing combustion. Simultaneously, it can participate in the curing of the pressure-sensitive adhesive in the form of hydroxy-isocyanate with ethyl acrylate isocyanate, increasing the curing speed while crosslinking with the original propylene network to form a double crosslinked structure, improving the cohesive strength of the pressure-sensitive adhesive, and thus enhancing its adhesion and holding power. The addition of alkenylated starch in this invention has a thickening effect, which improves the adhesion of the pressure-sensitive adhesive. It can also act as a char-forming agent, working synergistically with P and S in the functional monomers to improve the flame retardant effect of the pressure-sensitive adhesive.

[0007] Furthermore, the thickness of the fiberglass mesh is 15~30μm.

[0008] Furthermore, the amount of the flame-retardant pressure-sensitive adhesive applied in a single coat is 40~50g / m². 2 .

[0009] Furthermore, the aluminum foil has a thickness of 10~15μm.

[0010] Furthermore, the thickness of the carbon fiber membrane is 10~15μm.

[0011] Furthermore, the alkenylated starch is prepared by modifying starch using (S)-1,2-epoxy-5-hexene as a modifier. The specific preparation method is as follows: starch and sodium sulfate are added to water and mixed and stirred evenly to obtain a starch solution; the starch solution is heated to 40°C, sodium chloride is added, and stirred for 30 minutes; hydrogen peroxide with a mass concentration of 30% is added, and stirred for 5 hours; the pH is adjusted to 11 with sodium hydroxide solution; then sodium chloride and (S)-1,2-epoxy-5-hexene are added sequentially; after reacting at 40°C for 20 hours, the temperature is lowered to 25°C to 30°C; hydrochloric acid solution with a mass concentration of 20% is added to adjust the pH to 6.5; after the reaction is complete, the solid is obtained by filtration.

[0012] Furthermore, the functional monomer comprises, by weight, 10-15 parts of triallyl phosphate, 5-15 parts of vinyl sulfonic acid, and 5-10 parts of styrene.

[0013] Furthermore, the hydrotalcite and magnesium hydroxide are also surface-modified using an aminosilane coupling agent. The specific steps are as follows: hydrotalcite and magnesium hydroxide are added to a 15 vol% KH-550 / ethanol solution at a ratio of 0.1 g / mL, reacted for 5 h, and then the solid is taken and dried.

[0014] Furthermore, a method for preparing a double-sided flame-retardant aluminum foil reinforced composite film includes the following preparation steps: acrylic acid and hydroxyl silicone oil are mixed and dispersed evenly, heated to 70-80℃, and alkenylated starch and functional monomers are added at 100-200 rpm. The alkenylated starch is added in batches, 2-4 parts each time, followed by half of the initiator. After stirring and reacting for 30 minutes, hydrotalcite, magnesium hydroxide, and the remaining half of the initiator are added. After stirring and reacting for 1 hour, ethyl isocyanate acrylate is added, and the mixture is stirred for 10 minutes to obtain a flame-retardant pressure-sensitive adhesive. The flame-retardant pressure-sensitive adhesive is coated on one side of the aluminum foil, and then laminated with an equal area carbon fiber film to obtain a composite film. The flame-retardant pressure-sensitive adhesive is coated on both sides of a fiberglass mesh, and then a composite film of equal area is applied over the fiberglass mesh.

[0015] Compared with the prior art, the beneficial effects achieved by the present invention are: (1) This invention discloses a double-sided flame-retardant aluminum foil reinforced composite film material and its preparation method. The structure design of the scheme is reasonable. The product uses pressure-sensitive adhesive with excellent bonding and flame-retardant properties, so the peel strength between the aluminum foil surfaces is higher. At the same time, the product has excellent flame-retardant properties and is more practical.

[0016] (2) This method can prepare a flame-retardant pressure-sensitive adhesive with excellent flame retardancy, adhesion and tack by using appropriate amounts of alkenyl starch, monomer, hydroxyl silicone oil, ethyl isocyanate acrylate, hydrotalcite and magnesium hydroxide. While it is curing itself, it can also achieve double curing with hydroxy-isocyanate and amino-isocyanate, which can improve the curing speed and form a double cross-linking network to improve the cohesive strength of the pressure-sensitive adhesive. At the same time, the urea group and silane segment generated by the phenyl and amino-isocyanate in the monomer can improve the adhesion, high peel strength and flame retardancy. It can be prepared without any solvent and further prepared by combining with aluminum foil, glass fiber mesh and carbon fiber film to obtain the final product. Detailed Implementation

[0017] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention. Example 1

[0018] A method for preparing a double-sided flame-retardant aluminum foil reinforced composite film includes the following preparation steps: (1) Add starch and sodium sulfate to water, mix and stir evenly to obtain starch solution; heat starch solution to 40℃, add sodium chloride, stir for 30 minutes, add 30% hydrogen peroxide, stir for 5 hours, adjust pH to 11 with sodium hydroxide solution, then add sodium chloride and (S)-1,2-epoxy-5-hexene in sequence, react at 40℃ for 20 hours, then lower to 30℃, add 20% hydrochloric acid solution to adjust pH to 6.5, after the reaction is complete, filter to obtain solid alkenylated starch; (2) Mix and disperse acrylic acid and hydroxyl silicone oil evenly, heat to 75°C, add alkenylated starch and functional monomers at 200 rpm. Add alkenylated starch in batches, 4 parts each time, then add 1 / 2 of the initiator. After stirring and reacting for 30 min, add hydrotalcite, magnesium hydroxide, and the remaining 1 / 2 of the initiator. After stirring and reacting for 1 h, add ethyl isocyanate acrylate and stir for 10 min to obtain flame-retardant pressure-sensitive adhesive. Coat the flame-retardant pressure-sensitive adhesive on one side of a 15 μm thick aluminum foil, and composite it with a 15 μm thick carbon fiber film of equal area to obtain a composite film. Coat both sides of a 15 μm thick glass fiber mesh with flame-retardant pressure-sensitive adhesive, and cover it with a composite film of equal area. The single coating amount of flame-retardant pressure-sensitive adhesive is 40 g / m. 2 ; The flame-retardant pressure-sensitive adhesive comprises, by weight, 8 parts alkenylated starch, 25 parts functional monomers, 10 parts hydroxyl silicone oil, 10 parts ethyl isocyanate acrylate, 25 parts acrylic acid, 0.2 parts initiator, 3 parts hydrotalcite, and 3 parts magnesium hydroxide. The functional monomers comprise, by weight, 10 parts of triallyl phosphate, 5 parts of vinyl sulfonic acid, and 5 parts of styrene.

[0019] The hydrotalcite and magnesium hydroxide are further surface-modified using an aminosilane coupling agent. The specific steps are as follows: hydrotalcite and magnesium hydroxide are added to a 15 vol% KH-550 / ethanol solution at a ratio of 0.1 g / mL, reacted for 5 h, and then the solid is taken and dried. Example 2

[0020] The difference between Example 2 and Example 1 is that the flame-retardant pressure-sensitive adhesive, by weight, comprises 8 parts alkenylated starch, 28 parts functional monomers, 10 parts hydroxyl silicone oil, 12 parts ethyl isocyanate acrylate, 27 parts acrylic acid, 0.3 parts initiator, 4 parts hydrotalcite, and 4 parts magnesium hydroxide; the functional monomers, by weight, comprise 11 parts triallyl phosphate, 7 parts vinyl sulfonic acid, and 6 parts styrene. The remaining steps are the same as in Example 1. Example 3

[0021] The difference between Example 3 and Example 1 is that the flame-retardant pressure-sensitive adhesive, by weight, comprises 12 parts alkenylated starch, 30 parts functional monomers, 12 hydroxyl silicone oil, 15 parts ethyl isocyanate acrylate, 30 parts acrylic acid, 0.5 parts initiator, 6 parts hydrotalcite, and 6 parts magnesium hydroxide; the functional monomers, by weight, comprise 13 parts triallyl phosphate, 10 parts vinyl sulfonic acid, and 7 parts styrene. The remaining steps are the same as in Example 1. Example 4

[0022] The difference between Example 4 and Example 1 is that the flame-retardant pressure-sensitive adhesive, by weight, comprises 12 parts alkenylated starch, 32 parts functional monomers, 13 parts hydroxyl silicone oil, 17 parts ethyl isocyanate acrylate, 32 parts acrylic acid, 0.6 parts initiator, 7 parts hydrotalcite, and 7 parts magnesium hydroxide; the functional monomers, by weight, comprise 13 parts triallyl phosphate, 12 parts vinyl sulfonic acid, and 8 parts styrene. The remaining steps are the same as in Example 1. Example 5

[0023] The difference between Example 5 and Example 1 is that the flame-retardant pressure-sensitive adhesive, by weight, comprises 12 parts of alkenylated starch, 35 parts of functional monomers, 14 parts of hydroxyl silicone oil, 20 parts of ethyl isocyanate acrylate, 35 parts of acrylic acid, 1 part of initiator, 10 parts of hydrotalcite, and 10 parts of magnesium hydroxide; the functional monomers, by weight, comprise 15 parts of triallyl phosphate, 15 parts of vinyl sulfonic acid, and 10 parts of styrene. The remaining steps are the same as in Example 1.

[0024] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that alkenylated starch is not added. The remaining steps are the same as in Example 1.

[0025] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that ordinary starch is used instead of olefinized starch. The remaining steps are the same as in Example 1.

[0026] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that triallyl phosphate is not added. The remaining steps are the same as in Example 1.

[0027] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that vinyl sulfonic acid is not added. The remaining steps are the same as in Example 1.

[0028] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that styrene is not added. The remaining steps are the same as in Example 1.

[0029] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that hydroxyl silicone oil is not added. The remaining steps are the same as in Example 1.

[0030] Comparative Example 7 The difference between Comparative Example 7 and Example 1 is that ethyl isocyanate acrylate is not added. The remaining steps are the same as in Example 1.

[0031] Comparative Example 8 The difference between Comparative Example 8 and Example 1 is that no surface modification is performed on the hydrotalcite and magnesium hydroxide. The remaining steps are the same as in Example 1.

[0032] Testing experiment: 1. Take the reinforced composite membranes prepared in Examples 1-5 and Comparative Example 1, and test their limiting oxygen index according to the method disclosed in JC / T2028-2018 "Composite facing materials for mineral wool insulation products". Before the test, place the sample in deionized water and immerse it at a distance of 20 mm from the water surface for 15 min. After taking it out, wipe off the surface water, dry it in an oven at 105°C for 20 min, and cool it to room temperature (25°C). The specific data are shown in Table 1.

[0033] 2. Prepare composite films using the pressure-sensitive adhesives prepared in Examples 1-5 and Comparative Example 1. Coat one layer of the composite film with the same amount of flame-retardant pressure-sensitive adhesive. Lay the composite film onto the glass surface, roll it with an adhesive roller, and leave it for 30 minutes. Test its 180° peel strength. The tensile speed during the test is 300 mm / min. Take the average value of 5 tests. See Table 1 for details.

[0034] Table 1

[0035] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No markings in the claims should be construed as limiting the scope of the claims.

Claims

1. A double-sided flame-retardant aluminum foil reinforced composite film, comprising a composite film with fiberglass mesh as the substrate, coated on both sides with flame-retardant pressure-sensitive adhesive, and covering an area equal to that of the fiberglass mesh, characterized in that... The flame-retardant pressure-sensitive adhesive comprises, by weight, 8-12 parts alkenylated starch, 25-35 parts functional monomers, 10-14 parts hydroxyl silicone oil, 10-20 parts ethyl isocyanate acrylate, 25-35 parts acrylic acid, 0.2-1 parts initiator, 3-10 parts hydrotalcite, and 3-10 parts magnesium hydroxide. The alkenylated starch is prepared by modifying starch with (S)-1,2-epoxy-5-hexene. The functional monomers comprise, by weight, 10-15 parts triallyl phosphate, 5-15 parts vinyl sulfonic acid, and 5-10 parts styrene. The hydrotalcite and magnesium hydroxide are further surface-modified using an aminosilane coupling agent. The composite film is made by coating one side of an aluminum foil with a thickness of 10-15 μm with flame-retardant pressure-sensitive adhesive and then bonding it with a carbon fiber film of equal area and a thickness of 10-15 μm.

2. The double-sided flame-retardant aluminum foil reinforced composite film according to claim 1, characterized in that, The thickness of the fiberglass mesh is 15~30μm.

3. The double-sided flame-retardant aluminum foil reinforced composite film according to claim 1, characterized in that, The flame-retardant pressure-sensitive adhesive has a single coating amount of 40~50g / m². 2 .

4. The method for preparing a double-sided flame-retardant aluminum foil reinforced composite film according to claim 1, characterized in that, The preparation steps include: mixing and dispersing acrylic acid and hydroxyl silicone oil evenly, heating to 70~80℃, adding alkenylated starch and functional monomers at 100~200rpm, adding alkenylated starch in batches of 2~4 parts each time, then adding 1 / 2 of the initiator, stirring and reacting for 30min, then adding hydrotalcite, magnesium hydroxide, and the remaining 1 / 2 of the initiator, stirring and reacting for 1h, then adding ethyl isocyanate acrylate, stirring for 10min to obtain flame-retardant pressure-sensitive adhesive; coating the flame-retardant pressure-sensitive adhesive on one side of aluminum foil, and then laminating it with an equal area of ​​carbon fiber film to obtain a composite film; coating both sides of a fiberglass mesh with the flame-retardant pressure-sensitive adhesive, and then covering it with an equal area of ​​the composite film.

Citation Information

Patent Citations

  • Self-adhesion silicon rubber material and preparation method thereof

    CN106380860A

  • High-viscosity water-based pressure-sensitive adhesive for paper and preparation method thereof

    CN118109157A

  • Rib-clamping aluminum foil film

    CN218701810U

  • High-thermal-conductivity flame-retardant acrylic pressure-sensitive adhesive

    CN218989160U